Genetic insights into statin-associated diabetes risk - Swerdlow, DI; Preiss, D (Lippincott, Williams & Wilkins, 2016)
Purpose of review: Meta-analyses of major statin trials have suggested that statin therapy modestly increases the risk of developing diabetes. However, the quality of the data on which these findings are based is not without weaknesses and it has also been unclear whether this effect, if true, is an on-target or off-target effect of statins. Recent findings: In a major Mendelian randomization study of variants in the HMGCR gene, which encodes the protein through which statins exert their effect, two polymorphisms associated with lower LDL-cholesterol were also associated with higher weight, higher waist circumference, higher glucose and higher diabetes risk. These findings correspond with findings from the statin trials. In addition, new observational studies using a genetic risk score for LDL-cholesterol suggest that other pathways linked to LDL-cholesterol metabolism may also affect diabetes risk. Summary: Genetic studies indicate that the observed effect of statins on diabetes risk in trials is highly likely to be a true on-target effect. Although other recent studies have suggested that genetically determined lower LDL-cholesterol may be linked to diabetes risk, further data from both genetic studies and clinical trials of other LDL-cholesterol lowering agents are needed to confirm or refute this.